Early Statin Use and the Progression of Alzheimer Disease: A Total Population-Based Case-Control Study. Issue 47 (November 2015) - Lin, Feng-Cheng; Chuang, Yun-Shiuan; Hsieh, Hui-Min; Lee, Tzu-Chi; Chiu, Kuei-Fen; Liu, Ching-Kuan; Wu, Ming-Tsang
Abstract : Abstract: The protective effect of statin on Alzheimer disease (AD) is still controversial, probably due to the debate about when to start the use of statin and the lack of any large-scale randomized evidence that actually supports the hypothesis. The purpose of this study was to examine the protective effect of early statin use on mild-to-moderate AD in the total Taiwanese population. This was a total population-based case-control study, using the total population of Taiwanese citizens seen in general medical practice; therefore, the findings can be applied to the general population. The study patients were those with newly diagnosed dementia (ICD-9 290.x) and prescribed any acetylcholinesterase inhibitors (AChEI) from the Taiwan National Health Insurance dataset in 1997 to 2008. The newly diagnosed eligible mild-to-moderate AD patients were traced from the dates of their index dates, which was defined as the first day to receive any AChEI treatment, back to 1 year (exposure period) to categorize them into AD with early statin use and without early statin use. Early statin use was defined as patients using statin before AChEI treatment. Alzheimer disease patients with early statin use were those receiving any statin treatment during the exposure period. Then, we used propensity-score-matched strategy to match these 2 groups as 1:1. The matched study patients were followed-up from their index dates. The primary outcome was the discontinuation of AChEI treatment, indicating AD progression. There were 719 mild-to-moderate AD-paired patients with early statin use and without early statin use for analyses. Alzheimer disease progression was statistically lower in AD patients with early statin use than those without ( P  = 0.00054). After adjusting for other covariates, mild-to-moderate AD patients with early stain use exhibited a 0.85-risk (95% CI = 0.76–0.95, P  = 0.0066) to have AD progression than those without. Early statin use was significantly associated with a reduction in AD progression in mild-to-moderate AD patients. The future randomized trial studies can confirm our findings. Abstract : Supplemental Digital Content is available in the text